Use of contemporary prostate brachytherapy approaches in clinical trials. (January 2019) - Haworth, A; Sun, Y; Ebert, M; Reynolds, H; Betts, J; Wraith, D; Mitchell, C; Murphy, D; Parameswaran, B; Williams, S
Abstract: A number of clinical trials are investigating the role of prostate focal brachytherapy as an alternative treatment to whole gland therapy, offering the opportunity for tumour dose escalation and/or reduced toxicity. Brachytherapy, either low dose rate or high dose rate, offers a treatment choice with both precision in dose delivery and opportunity for a highly conformal, non-uniform dose distribution. Whilst multiple consensus documents have published clinical guidelines for patient selection, there are insufficient data to provide clear guidelines for treatment planning approaches along with many other technical issues when practicing focal brachy-therapy. Without consensus guidelines there is the potential for a diversity of practices to develop, leading to challenges in interpreting outcome data from multiple centres. We provide a quantitative framework for prostate focal brachytherapy that incorporates a personalized, biological approach that can be used as the foundation for future prostate focal brachytherapy trials.